FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI IBU BERSALIN DALAM MEMILIH PERTOLONGAN PERSALINAN DI WILAYAH KERJA PUSKESMAS KAMPUNG LAUT KECAMATAN KUALA JAMBI TAHUN 2025 - Intan Adelia (Jurnal Penelitian Kesmasy, 2026)
Providing various services for pregnant women, mothers giving birth, and postpartum mothers, such as pregnancy classes, tetanus immunizations, and reproductive health education in schools, is a crucial step in reducing maternal mortality. A crucial support that must be provided to mothers giving birth is assistance with deliveries by health workers. According to a report from the Jambi Provincial Health Office, in 2022, there were 60,165 deliveries recorded, 91% of which were handled by medical personnel. Of these, 57,012 deliveries (86.24%) took place in health facilities, while 3,150 deliveries (4.76%) were assisted by health workers outside these facilities. It is known that 589 deliveries (0.89%) were assisted by non-medical personnel, such as traditional birth attendants. The Kampung Laut Community Health Center is located in Kuala Jambi District, East Tanjung Jabung Regency. In 2022, approximately 22.78% of mothers gave birth with the assistance of non-health workers, where the delivery process took place outside of a health facility. This study aims to determine the factors that influence mothers in choosing the type of delivery assistance. The population in this study were all mothers giving birth who live in the working area of ​​the Kampung Laut Community Health Center, totaling 249 people, with a sample size of 70 mothers. Data were collected through interviews using a questionnaire instrument. To examine the factors that influence mothers' perceptions in choosing delivery assistance, chi-square statistical analysis was used. Data analysis consisted of univariate and bivariate analysis. The results showed that there was a relationship between knowledge and perception of mothers giving birth (p value = 0.003), mother's perception (p value = 0.005), income (p value = 0.008), family support (p value = 0.009), experience (p value = 0.021), there was no relationship between culture and perception of pregnant women (p value = 0.531) and midwife's attitude with perception of pregnant women (p value = 0.51).